Depreciation Accounting and the Anomalous Self-Insurance Cost. - Cramer, Jr., Joe J.; Schrader, William J. (The Accounting Review, 1970)
The article evaluates the method of determining the depreciation rate for a group account in order to draw conclusions regarding its relevancy as an approach to self-insurance expense and depreciation accounting. In an attempt to minimize costs associated with formal insurance contracts (exchange transaction) some companies implement programs of self-insurance. In contemporary accounting practice, events to be recognized in the accounts must be characterized by exchanges of consideration. Orthodox procedure for recognizing gains or losses resulting from casualties distorts the proportionate allocation of costs over the relevant planning horizon or period for which a group of assets is expected to produce revenues as judged by management at the time the decision is made to acquire the assets. In the above discussion it has been demonstrated that the notion of self-insurance expense is incompatible with contemporary accounting practices. Recognition of this fictitious cost does not meet the criterion of exchange transaction as required by contemporary accounting practices.